2021
DOI: 10.11604/pamj.2021.38.246.28169
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characteristics and outcomes of patients hospitalized for COVID-19 in Douala, Cameroon

Abstract: Introduction the coronavirus disease (COVID-19) is a disease that originated from Wuhan in December 2019. It rapidly spread across the globe causing high mortality especially among the elderly. Africa though not spared has limited studies regarding its effects on its population. We therefore sought to describe the epidemiological and clinical characteristics of COVID-19 in Douala, Cameroon. Methods we conducted a single-centre, retrospective, and observational study by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
(24 reference statements)
2
12
1
Order By: Relevance
“…A higher proportion of patients presenting to MNRH CTU had severe/critical illness compared to those in our setting (>80% versus 52%), and challenges related to late presentation and shortage of oxygen and healthcare workers were also reported to have contributed to the high mortality in public health facilities across Uganda. Mortality reported in our study is also much lower than the 32% reported in Cameroon [ 25 ], and 48·2% in a cohort study of over 3,000 critically ill patients with COVID-19 pneumonia enrolled in 64 hospitals in ten African countries [ 26 ]. In the latter study, in addition to the traditional risk factors for adverse COVID-19 outcome, persons living with HIV/AIDS and those who experienced delayed access to high-care units and ICU had higher mortality rates.…”
Section: Discussioncontrasting
confidence: 51%
“…A higher proportion of patients presenting to MNRH CTU had severe/critical illness compared to those in our setting (>80% versus 52%), and challenges related to late presentation and shortage of oxygen and healthcare workers were also reported to have contributed to the high mortality in public health facilities across Uganda. Mortality reported in our study is also much lower than the 32% reported in Cameroon [ 25 ], and 48·2% in a cohort study of over 3,000 critically ill patients with COVID-19 pneumonia enrolled in 64 hospitals in ten African countries [ 26 ]. In the latter study, in addition to the traditional risk factors for adverse COVID-19 outcome, persons living with HIV/AIDS and those who experienced delayed access to high-care units and ICU had higher mortality rates.…”
Section: Discussioncontrasting
confidence: 51%
“…For these reasons, we expected all these factors to contribute to an escalation of the transmission of COVID-19 in Cameroon. Unfortunately, less than 3.9% of scientific reports on COVID-19 have originated from Africa [8] and very few from Cameroon [9]. To fill this gap, the study sought to describe clinical features of COVID-19 infection and risk factors for patients admitted in the Djoungolo Hospital COVID-19 treatment centre in Cameroon.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the patients had at least two comorbidities which were represented by hypertension, diabetes and obesity. In Douala, Mekolo et al and Mbarga et al found high prevalence of hypertension and diabetes in patients hospitalized and suspected for COVID-19 in Douala and Yaoundé towns, respectively[8,9]. Similarly, obesity was reported in > 20% of…”
mentioning
confidence: 99%
“…Even though reports point out the increasing burden of the above mentioned comorbidities in sSA countries, very few studies on COVID-19, associated factors, and the role of these comorbidities have been conducted in the continent, especially in Cameroon [8][9][10][11]. Diabetes and hepatitis B virus (HBV) infection are increasingly documented at significant rates in African populations, and few studies outlined increased risk of COVID-19 related complications and death in African patients suffering from diabetes and chronic HBV infection [9,12,13].…”
mentioning
confidence: 99%